EKSPLORASI DAN KOLEKSI JAMUR (MUSROOM) PADA KAWASAN TAMAN NASIONAL BOGANI NANI WARTABONE, SULAWESI UTARA - Arwan Sugiharto (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2010)
The exploration have been done to collect and to know variety and existence of edible mushroom in Toraut Village, Boganinani Wartabone, National Park in North of Sulawesi. The result of identified found 12 mushroom at primary and secondary forest ecosystem. There are in genus of Clitocybe, Ganoderma, Fomes, Piptoporus, Daldinia, Heterobasidium, Phellinus, Polyporus, Auricularia, Trametes, Coltricia. Only 2 edible mushroom become one of the food source for local society, Clitocybe odora and Auricularia sp.